MRI compatible head phantom for ultrasound surgery - Menikou, Georgios; Dadakova, Tetiana; Pavlina, Matt; Bock, Michael; Damianou, Christakis A. (My University, 2015)
Objective: Develop a magnetic resonance imaging (MRI) compatible head phantom with acoustic attenuation closely matched to the human attenuation, and suitable for testing focused ultrasound surgery protocols. Materials and methods: Images from an adult brain CT scan were used to segment the skull bone from adjacent cerebral tissue. The segmented model was manufactured in a 3-D printer using (Acrylonitrile Butadiene Styrene) ABS plastic. The cerebral tissue was mimicked by an agar-evaporated milk-silica gel (2% w/v-25% v/v-1.2% w/v) which was molded inside a skull model. Results: The measured attenuation of the ABS skull was 16 dB/cm MHz. The estimated attenuation coefficient of the gel replicating brain tissue was 0.6 dB/cm MHz. The estimated agar-silica gel's T1 and T2 relaxation times in a 1.5 Tesla magnetic field were 852 ms and 66 ms respectively. The effectiveness of the skull to reduce ultrasonic heating was demonstrated using MRI thermometry. Conclusion: Due to growing interest in using MRI guided focused ultrasound (MRgFUS) for treating brain cancer and its application in sonothrombolysis, the proposed head phantom can be utilized as a very useful tool for evaluating ultrasonic protocols, thus minimizing the need for animal models and cadavers.
Keywords: Brain; MRI; Ultrasound